Correlation between type of surgery and incidence of postoperative venous thromboembolism (VTE) - Supomo; Budi Mulyono; Usi Sukorini; Adika Zhulhi Arjana; Tandean Tommy Novenanto (Published by Universitas Gadjah Mada, 2024)
Venous thromboembolism (VTE) is a significant complication in patients after undergoing major surgery. The type of surgery is believed correlated with the incidence of VTE. This study aimed to evaluate the correlation between type of surgery and incidence of VTE among patients who underwent major surgery. It was a retrospective study conducted in Dr. Sardjito General Hospital, Yogyakarta using medical record data of patients who underwent major surgery and were diagnosed with VTE between 2016 and 2020. Patients were grouped by surgery type, and length of stay (LoS). All caused deaths were also analyzed. Among 29,120 patients who underwent major surgery, 76 (0.26%) experienced VTE with females patients accounting for 75%. The mean age of the patients was 55 yr. All VTE cases had the mean LoS of 25 d. The highest proportion of patients who experienced VTE were patients who underwent tumor removal (67.0%) followed by trauma patients (18.4%). A significant difference in the incidence of mortality between the surgical groups was reported (p = 0.02). Post-cardiology had the highest risk of mortality (OR=7.46; 95% CI: 0.322 - 172.61) while age had the lowest risk of mortality (OR=1.01; 95% CI: 0.953 - 1.071). In conclusion, surgery type is correlated with the incidence of VTE. Surgery due to cancer and trauma has a higher risk of VTE compared to the others.